O novo paradigma pós-teísta: Por um novo diálogo entre as religiões - Cugini, Paolo (Revista Eclesiástica Brasileira, 2023)
Este artigo pretende apresentar e aprofundar a proposta que atende pelo nome de pós-teísmo. Para atingir o objetivo, são examinados os escritos dos principais autores que estão refletindo sobre o que se define a um novo paradigma. Assim, examinam-se as análises de, entre outros: Spong, Lenaers, Arregi, Vigil, Gamberini Fanti, Boff. Após uma breve análise historiográfica do conceito de teísmo, a reflexão se concentra em analisar o destino do cristianismo na atual situação pós-teísta. O sentimento que emerge da análise dos textos é que a proposta pós-teísta saúda definitivamente a leitura teísta que a Igreja propôs nos primeiros séculos do mistério cristão. O caminho que se propõe no novo marco cultural pós-teísta consiste na capacidade de olhar e ir além do cristianismo, da religião e do próprio Deus. Indicações para uma nova espiritualidade capaz de integrar a contribuição das disciplinas científicas. Na fase final, além da coragem de ter aberto novas perspectivas espirituais, destacam-se algumas limitações na abordagem e na tomada de posições. Interroga-se sobre a falta de escrúpulos com que o pós-teísmo identifica a verdade com a ciência, além de duvidar da reconstrução histórica da evolução do teísmo e seus corolários culturais. Abstract: This article intends to present and deepen the proposal that goes by the name of post-theism. To achieve the goal, the writings of the main authors who are reflecting on what is defined as a new paradigm are examined. Thus, the analyses of, among others, are examined: Spong, Lenaers, Arregi, Vigil, Gamberini Fanti, Boff. After a brief historiographical analysis of the concept of theism, the reflection focuses on analysing the fate of Christianity in the current post-theistic situation. The feeling that emerges in the analysis of the texts is that the post-theistic proposal definitively greets the theistic reading that the Church proposed in the first centuries of the Christian mystery. The path that is proposed in the new post-theistic cultural framework consists in the ability to look and go beyond Christianity, religion and beyond God himself. The awareness of the epochal cultural turning point we are experiencing leads the authors of post-theism to elaborate indications for a new spirituality capable of integrating the contribution of scientific disciplines. In the final phase, in addition to the courage of having opened up new spiritual perspectives, some limitations in the approach and in taking positions are underlined. One wonders about the unscrupulousness with which post-theism identifies truth with science, as well as harbouring doubts about the historical reconstruction of the evolution of theism and its cultural corollaries. Keywords: Theism; Paradigm; Dualism; Monism; Christianity.